2022
DOI: 10.3389/fpubh.2022.1039680
|View full text |Cite
|
Sign up to set email alerts
|

Industrial exoskeletons from bench to field: Human-machine interface and user experience in occupational settings and tasks

Abstract: ObjectiveWork-related musculoskeletal disorders (WRMSDs) are considered nowadays the most serious issue in the Occupational Health and Safety field and industrial exoskeletons appear to be a new approach to addressing this medical burden. A systematic review has been carried out to analyze the real-life data of the application of exoskeletons in work settings considering the subjective responses of workers.MethodsThe review was registered on PROSPERO. The literature search and its report have been performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…According to the most recent review of field studies [ 10 ], usability was moderate to high for all types of EXO-ASE evaluated. However, the overall acceptance of exoskeletons in the occupational context is a complex phenomenon related to technology-induced self-efficacy beliefs, which in turn are modulated by the ability to reduce effort and the attributed utility of the device [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the most recent review of field studies [ 10 ], usability was moderate to high for all types of EXO-ASE evaluated. However, the overall acceptance of exoskeletons in the occupational context is a complex phenomenon related to technology-induced self-efficacy beliefs, which in turn are modulated by the ability to reduce effort and the attributed utility of the device [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the review by Baldassarre et al (2022) [ 10 ], some authors report an increase in the perceived discomfort level by workers during exoskeleton use, especially in dynamic tasks. This effect is associated with friction, pressure, or thermal discomfort caused by the device under specific working conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing evidence suggests that exoskeletons can potentially reduce WMSD risk. Further, the studies revealed that exoskeletons tend to show more of their potential in static activities, while in dynamic tasks, they can hinder regular job performance (Baldassarre et al, 2022 ). Thus, more research is required to understand how exoskeletons can be adapted to different tasks and work environments.…”
Section: Introductionmentioning
confidence: 99%